Review on CO2 capture by blended amine solutions - Aghel, Babak; Janati, Sara; Wongwises, Somchai; Shadloo, Mostafa Safdari (International journal of greenhouse gas control, 2022)
•The role of blended solvents, their advantages, and disadvantages in the CO2 capture•Investigation of the chemical adsorption process of CO2 in different types of the mixture, and technical-energy analysis•The current limitations and challenges of amine mixtures in CO2 capture The procedure of CO2 removal through the absorption/desorption system based on chemical amine solvents offers an interesting commercial technology to absorb CO2. However, it has a major drawback regarding the high energy required in the regeneration of the solvent, which has turned into the most important challenge of chemical absorption procedures. Through precise analysis and integration of the rise in CO2 absorption with energy consumption in the desorption process, this review article has investigated two approaches. The first approach evaluates the development of solvents and the use of amine blends in four forms, i.e., aqueous solutions, non-aqueous solutions, two-phase blends, and ionic blends, with high capacity and absorption. The second approach discusses the changes in operational conditions, process modifications, and integration of thermal power plants to improve efficiency and reduce the high energy demand for PCC technologies. Moreover, an effort has been made to help further the development of absorption technology by presenting future perspectives considering the current condition of absorption, the barriers of amine scrubbing in steam boilers, and reduced thermal efficiency. [Display omitted]